Factors Associated with Successful Tuberculosis Treatment in the Primary Health Care of Bekasi - Kartika Putri Amalia; Sri Rahayu; Erna Harfiani (Universitas Ahmad Dahlan, 2022)
Background: Tuberculosis is still a significant disease problem globally as it is one of ten causes of death worldwide and in Indonesia. Bekasi is the second-largest city with tuberculosis patients after Bandung, with 3,355 patients in 2015. The success rate of treatment that has not reached the standard in the primary health care of Bekasi, West Java, can be related to medication adherence, age, and nutritional status. Inadequate nutritional intake in tuberculosis patients will increase the recovery time. The more days of irregularity in taking the drug increases the likelihood of the patient having a default that can lead to drug-resistant tuberculosis. This study aimed to determine the correlation between anti-tuberculosis drug adherence, age, and nutritional status with tuberculosis treatment in new tuberculosis cases in the primary health care of Bekasi. Method: This was analytic observational research with a cross-sectional design study in 311 new tuberculosis cases at 30 primary health care in Bekasi city period 2015. Data were analyzed using univariate data and then continued with the chi-square test and logistic regression test. Results: The results of the univariate analysis were found to obtain patients' compliance by 84.9% adherent, productive age (91%), and nutritional status with IMT under 18.5 kg/m2 (68.8%). Chi-square test shown there was a significant relationship between medication adherence (p-value = 0.000; OR = 5917.5; 95%CI = 525.57 – 66626.6), age (p-value = 0.003; OR = 3.81; 95%CI = 1.63 – 8.90), and nutritional status (p-value = 0.000; OR = 7.88; 95%CI = 2.38 – 26.08) with therapeutic outcome. Logistic regression analysis showed that anti-tuberculosis drug adherence (p-value = 0.000; OR = 5917.5) was the most dominant variable related to tuberculosis treatment success. Conclusion: We conclude that the success of tuberculosis treatment in the primary health care of the Bekasi period 2015 relates to anti-tuberculosis drug (medication) adherence, age, and nutritional status, while medication adherence has the most significant influence on the success of tuberculosis treatment.